Targeting sphingosine 1-phosphate receptor 3 inhibits T-cell exhaustion and regulates recruitment of proinflammatory macrophages to improve antitumor efficacy of CAR-T cells against solid tumor - Weiting Liao; Ge Gao; Xia He; Pei Shu; Qizhi Ma; Benxia Zhang; Diyuan Qin; Yongsheng Wang (Journal for ImmunoTherapy of Cancer)
Backgrounds Chimeric antigen receptor (CAR)-modified T cells (CAR-T) are limited in solid tumors due to the hostile tumor microenvironment (TME). Combination therapy could be a promising approach to overcome this obstacle. Recent studies have shown that sphingosine 1-phosphate receptor (S1PR)3 has tremendous potential in regulating the immune environment. However, the functional significance of S1PR3 in T-cell-based immunotherapies and the molecular mechanisms have not been fully understood.Methods Here, we studied the combination of EpCAM-specific CAR T-cell therapy with pharmacological blockade of S1PR3 against solid tumor. We have applied RNA sequencing, flow cytometry, ELISA, cellular/molecular immunological technology, and mouse models of solid cancers.Results Our study provided evidence that S1PR3 high expression is positively associated with resistance to programmed cell death protein-1 (PD-1)-based immunotherapy and increased T-cell exhaustion. In addition, pharmacological inhibition of S1PR3 improves the efficacy of anti-PD-1 therapy. Next, we explored the possible combination of S1PR3 antagonist with murine EpCAM-targeted CAR-T cells in immunocompetent mouse models of breast cancer and colon cancer. The results indicated that the S1PR3 antagonist could significantly enhance the efficacy of murine EpCAM CAR-T cells in vitro and in vivo. Mechanistically, the S1PR3 antagonist improved CAR-T cell activation, regulated the central memory phenotype, and reduced CAR-T cell exhaustion in vitro. Targeting S1PR3 was shown to remodel the TME through the recruitment of proinflammatory macrophages by promoting macrophage activation and proinflammatory phenotype polarization, resulting in improved CAR-T cell infiltration and amplified recruitment of CD8+T cells.Conclusions This work demonstrated targeting S1PR3 could increase the antitumor activities of CAR-T cell therapy at least partially by inhibiting T-cell exhaustion and remodeling the TME through the recruitment of proinflammatory macrophages. These findings provided additional rationale for combining S1PR3 inhibitor with CAR-T cells for the treatment of solid tumor.